Additive Manufacturing of Ceramic-Based Materials - Travitzky, Nahum; Bonet, Alexander; Dermeik, Benjamin; Fey, Tobias; Filbert-Demut, Ina; Schlier, Lorenz; Schlordt, Tobias; Greil, Peter (Advanced Engineering Materials, 2014)
This paper offers a review of present achievements in the field of processing of ceramic-based materials with complex geometry using the main additive manufacturing (AM) technologies. In AM, the geometrical design of a desired ceramic-based component is combined with the materials design. In this way, the fabrication times and the product costs of ceramic-based parts with required properties can be substantially reduced. However, dimensional accuracy and surface finish still remain crucial features in today's AM due to the layer-by-layer formation of the parts. In spite of the fact that significant progress has been made in the development of feedstock materials, the most difficult limitations for AM technologies are the restrictions set by material selection for each AM method and aspects considering the inner architectural design of the manufactured parts. Hence, any future progress in the field of AM should be based on the improvement of the existing technologies or, alternatively, the development of new approaches with an emphasis on parts allowing the near-net formation of ceramic structures, while optimizing the design of new materials and of the part architecture.

Highly Filled Papers, on their Manufacturing, Processing, and Applications - Dermeik, Benjamin; Lorenz, Hannes; Bonet, Alexander; Travitzky, Nahum (Advanced Engineering Materials, 2019)
Since more than a decade ago, the research on highly filled papers, as well as paper-derived inorganic materials, has greatly intensified. As presented in this review, highly filled papers as preforms allow for the design of porous or dense, multilayered, and geometrically complex structures. These paper-derived ceramic- or metal-based materials are generated by the heat-treatment of highly filled papers. Paper-derived materials are potential materials of choice for applications in transportation, energy-generation, environmental conservation, support structures, medical uses, and electronic components. Due to the adjustability of the filler content and the good machinability of highly filled papers, paper-derived sheets or multilayers may include intricate structures and tailored gradients in phase structure or porosity. Paper-derived multilayers also may contain cast ceramic tapes or other functionalized layers, as presented in some examples. Computer-aided manufacturing processes for paper-derived materials can be supplemented by prediction models for the sintering shrinkage in order to identify optimal post-processing steps, stacking orders and orientations for highly filled paper layers within multilayer green bodies. The accuracy of established component-level sintering models can be significantly increased by microstructure models of the highly filled paper.
CRIS-Team Scopus Importer:2019-06-28

Influence of calendering on the properties of paper-derived alumina ceramics - Schlordt, Tobias; Dermeik, Benjamin; Beil, Veronika; Freihart, Matthias; Hofenauer, Andreas; Travitzky, Nahum; Greil, Peter (Ceramics International, 2013)
The effect of calendering of alumina loaded preceramic papers in a hard nip laboratory calender at various temperatures, line loads and times of nip passes on their green and sintered properties was investigated. The main objective was to achieve a maximum densification, which resulted in a maximum reduction of thickness of 45%, a green density of 80.5% of the theoretical density and a sintered density of 81% of the theoretical density. The ring-on-ring flexural strength of sintered specimen could be increased from 71±11 MPa to 138±33 MPa. The surface roughness of green samples could be diminished to a value for Ra of below 2 µm compared to an Ra of 13.2 µm for an uncalendered paper, whereas the Ra value of the sintered samples was much higher due to the burn-off of the cellulose fibers. Preceramic papers manufactured by the dynamic hand-sheet-forming process exhibit a fiber-orientation which causes anisotropic effects regarding the sintering shrinkage, the surface roughness and Young's modulus.
Keywords: Porosity; Surfaces; Mechanical properties; Preceramic paper

Influence of coatings on microstructure and mechanical properties of preceramic paper-derived porous alumina substrates - Junkes, Janaína Accordi; Dermeik, Benjamin; Gutbrod, Björn; Hotza, Dachamir; Greil, Peter; Travitzky, Nahum (Journal of Materials Processing Technology, 2013)
Preceramic papers loaded with inorganic fillers may be used as preforms in a novel manufacturing technique to fabricate lightweight ceramic structures. In order to reduce the porosity caused by burning out cellulosic fibers and organics, porous preceramic paper-derived alumina substrates were post-treated via two different coating routes using silica suspension or methylphenylvinylhydrogen polysiloxane. Sintering of the alumina-filled preceramic papers in air at 1600 °C for 2 h resulted in a non-uniform distributed open porosity ranging from 23 to 26%. After coating and infiltration, all samples were additionally heat treated up to at 1500 °C for 2 h. Thermal analysis (DTA/TG) was applied to determine the pyrolysis temperature of polysiloxane. Microstructure and phase analysis were performed respectively by SEM and XRD. After sintering, water absorption, apparent density and open porosity of test pieces were determined, and mechanical properties of the substrates were evaluated before and after coating. For the samples coated with silica suspension, the mechanical strength remained in the same range of those for uncoated samples, while for the polysiloxane coated samples the mechanical strength steadily increases after repeated impregnation steps, reaching 350 MPa.
Keywords: Preceramic paper; Coating; Infiltration; Mechanical properties; Alumina; Silica

Laminated Object Manufacturing of Ceramic-Based Materials - Dermeik, Benjamin; Travitzky, Nahum (Advanced Engineering Materials, 2020)
Since their inception, additive manufacturing (AM) techniques have been the go-to methods for obtaining highly complex-shaped rapid prototypes (RPs) and specialized parts, which were produced in small lot sizes. The AM technique of laminated object manufacturing (LOM) is an immensely convenient and cost-effective method for quickly producing millimeter-sized to meter-sized parts, while incorporating micrometer-sized constructive features. LOM machines offer an open work space, within which nontoxic and highly filled sheet materials can be processed at a high production velocity. The unique property profile of ceramic-based materials from LOM may be indispensable for applications calling for materials that unite high temperature resistance, mechanical strength, and light weight. Optionally, local material functionalization may engender the electrical conductivity, chemical stability, ferroelectricity, radiation shielding, or filter membrane stability of a limited portion of the material. Herein, a detailed evaluation of the applicability of LOM in the near net shaping ceramic-based materials is presented. Optional technical adjustments for the LOM process and extensions of the LOM machine configuration can improve the economic feasibility its operation. Previously successful LOM-printed ceramic-based materials are showcased within a comprehensive overview on the state of the art and potential novel composite materials are presented.
CRIS-Team Scopus Importer:2020-06-02
Keywords: additive manufacturing; ceramic matrix composites; ceramic-based materials; laminated object manufacturing; paper-derived ceramics

Processing and characterization of paper-derived Ti3SiC2 based ceramic - Travitzky, Nahum; Dermeik, Benjamin; Hock, Nils; Greil, Peter; Schulheiss, Jan; Yin, Xiaowei; Filbert-Demut, Ina (Ceramics International, 2015)
Porous layers of paper-derived titanium silicon carbide (Ti3SiC2), with a thickness ranging from 300 to 700μm, were obtained by the heat treatment of preceramic papers containing Ti3SiC2 as filler particles. The tearing strength of the preceramic papers was provided by cellulose fibers obtained from wood by the kraft pulping process, also described as pulp fibers, and ionic starches. Short pulp fibers with an average length of 657μm were derived from short fibered hardwood (eucalyptus), while long pulp fibers with an average length of 1665μm were derived from long fibered softwood (spruce, pine and larch). The fiber length of pulp fibers in the preceramic papers also influenced the microstructure and the properties of the paper-derived Ti3SiC2. Preceramic papers fabricated with short pulp fibers exclusively led to an average porosity of 18.6vol% for the paper-derived Ti3SiC2, whereas the paper-derived Ti3SiC2 had an average porosity of 45.3vol% when preceramic papers with long pulp fibers only were used. The density of the paper-derived Ti3SiC2 also affected the flexural strength, as could be shown by densifying preceramic papers using a calender. Thereby, the flexural strength of paper-derived Ti3SiC2 could be increased by more than five times, from 13MPa to 83MPa. The purity of the paper-derived Ti3SiC2 was found to be dependent on the purity of the raw materials and the process cycle, with TiC x and Al2O3 impurities present in the ceramics.
Keywords: A. Shaping; A. Sintering; C. Mechanical properties; D. Carbides; MAX-phase

Processing, Microstructure and Properties of Paper-Derived Porous Al2O3 Substrates - Kluthe, Christopher; Dermeik, Benjamin; Kollenberg, Wolfgang; Greil, Peter; Travitzky, Nahum (Journal of Ceramic Science and Technology, 2012)
In this work, preceramic papers containing 85 wt% Al2O3 were heat-treated at 1600 °C to obtain paper-derived ceramics. In order to increase the preceramic paper density prior to sintering, the papers were calendered at different roll temperatures and pressures. The influences of the calendering parameters on the microstructure and mechanical properties of the preceramic papers and the paper-derived ceramics were investigated. It was expected that especially the mechanical properties of the papers and derived ceramics would be improved by calendering. The increase in the preceramic paper density led to an increase by 85 % of the green tensile strength from 20 MPa to 37 MPa in cross direction (CD) and by 91 %, from 11 MPa to  21 MPa in machining direction (MD). An increase in flexural strength by  96 %, from 138 MPa to 270 MPa, was obtained for the paper-derived ceramics with an increase in density by 25 %, from 2.4 g/cm³ to 3.0 g/cm³, and the shrinkage after sintering was reduced from 15 % to 12 % owing to the previous calendering of the preceramic paper.
Keywords: Preceramic paper; calendering; mechanical properties; sintering; porosity

Sintering simulations for ceramic multilayer laminates with paper-derived ceramics: From sintering dilatometry to anisotropic sintering simulation - Manière, Charles; Lecourt, Jérome; Dermeik, Benjamin; Schmiedeke, Samuel; Travitzky, Nahum (Journal of the European Ceramic Society, 2024)
Alumina-based multilayer laminates with layers of varied porosities and ceramic fiber reinforcements, which can be achieved by including paper-derived ceramic layers, are interesting candidates for chemically stable and thermal shock resistant materials. In order to investigate the complex sintering behavior of these laminates, the sintering of each alumina layer contained within a laminate, each one with its individual sintering anisotropy and sintering shrinkage, has to be considered separately. For this purpose, sintering curves are determined by dilatometry measurements, serving a consecutive examination by an analytical model. Modeling parameters specific to each layer, are applied in finite-element-type sintering simulations for symmetrical multilayer laminates. Differences in the sintering shrinkages may cause internal stresses at layer interfaces and, in turn, may influence the thermal and mechanical properties of multilayer laminates after sintering. Accordingly, the prediction of developing internal stresses within alumina-based multilayer laminates by the presented sintering simulations is a key aspect of this study.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Anisotropy; Ceramics; Finite Element Method; Laminates; Simulation; Sintering